Geophysical models of Drake passage and Bransfield strait crustal structure - Levashov, S.P.; Yakymchuk, N.A.; Korchagin, I.N.; Bakhmutov, V.G.; Solovyov, V.D.; Kozlenko, Yu.V. (Український антарктичний журнал, 2008)
The 2004 (9th) and 2006 (11th) Ukrainian Antarctic expeditions acquired new geoelectrical data (‘short-impulse electromagnetic field formation’ – FSPEF, and ‘vertical electric-resonance sounding’ – VERS) along profiles across Drake Passage and along Bransfield Strait, Antarctic Peninsula, with the aim of studying the crustal structure of these features down to depths of >30 km.